Change of Retinal Vessel Density After Lowering Intraocular Pressure in Ocular Hypertension - Chen, Xuhao; Hong, Ying; Di, Haohao; Wu, Qianru; Zhang, Di; Zhang, Chun (Frontiers in Medicine, 2021)
Purpose: To investigate the relationship between retinal microvasculature changes and intraocular pressure (IOP) for ocular hypertension (OHT) patients and further assess the factors associated with retinal microcirculation changes. Methods: This was a single-center prospective study designed for OHT patients, which consisted of two visits. After collecting baseline data of those who met the eligibility criteria, these patients were treated with latanoprost 0.005% ophthalmic solution for 4 weeks. Peripapillary vessel density (VD) of radial peripapillary capillaries (RPC) layer, macular VD in both superficial and deep layers, and foveal avascular zone (FAZ) area were measured by optical coherence tomography angiography (OCTA) before and after the treatment. We compared the changes in IOP and VD among the two visits by paired-sample t-test. Bonferroni correction was applied. Factors associated with VD changes were analyzed by linear regression analysis. Results: Thirty-four eyes of thirty-four patients were included. The mean IOP decreased by 6.5 ± 2.2 mmHg (p < 0.001). The peripapillary RPC VD increased significantly from 51.8 ± 2.5 to 53.0 ± 3.1% (Adjusted-p = 0.012). We found no significant difference in detailed sectors of the peripapillary region after correction. In the macular area, both the superficial and deep layers in foveal (superficial: 0.2 ± 1.9%, p = 0.523; deep: 0.0 ± 2.3%, p = 0.969) and parafoveal (superficial: 0.3 ± 3.0%, p = 0.565; deep: 0.5 ± 3.1%, p = 0.423) VD remained unchanged. The decrease of the mean FAZ area was insignificant (p = 0.295). The percentage of IOP reduction (β = 0.330, p = 0.031) and the baseline RNFL thickness (β = 0.450, p = 0.004) significantly correlated with the percentage of peripapillary RPC VD improvement in the multivariate linear regression analysis. Conclusion: The peripapillary VD in OHT patients increased after the reduction of IOP. The mild change of IOP did not alter the microcirculation in the macula. In addition, the percentage of IOP change and the baseline RNFL thickness were independent factors for the peripapillary RPC VD improvement.